INFORMATION SYSTEM FOR STUDENTS AND TEACHERS INTERACTION BASED ON ANDROID APPLICATION (Modern information system and technologies, 2018)
The article presents a mobile application for improving the interaction between students and teachers. The functions and principles of operation and main components of the application are revealed.